Pengaruh Profitabilitas, Ukuran Perusahaan dan Kepemilikan Publik Terhadap Nilai Perusahaan (Studi Pada Perusahaan Consumer Goods Industry yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2020) - Vivi Adeyani Tandean (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2022)
Consumer goods industry companies are one of the sectors that are quite attractive to investors to invest. The purpose of this study was to examine the effect of profitability, firm size and public ownership on firm value. The research population uses consumer goods industry companies listed on the Indonesia Stock Exchange from 2016 to 2020. The number of samples used is 23 companies with purposive sampling method criteria so that the financial statements processed and analyzed are 115 data. The data in the study were processed using Eviews version 10. The results showed that profitability and firm size partially affected firm value, while public ownership had no effect on firm value partially.